Traceless Staudinger Ligation for Bioconjugation of RNA. Issue 2 (16th February 2021) - Kitoun, Camélia; Fonvielle, Matthieu; Arthur, Michel; Etheve‐Quelquejeu, Mélanie; Iannazzo, Laura
Abstract: Staudinger ligation is an attractive bioorthogonal reaction for use in studying biomolecules due to its capacity to form a native amide bond between a tag and a biomolecule. Here, we explore the traceless variant of the Staudinger ligation for 3′‐end modification of oligoribonucleotides. The procedure involves (i) synthesis of phosphine‐containing reactive groups, affinity purification tags, or photoactivatable benzophenone probe, (ii) synthesis of 2′‐azido dinucleotides and 24‐nt RNA, and (iii) traceless Staudinger ligation experiments. Each phosphine was characterized by 1 H, 13 C, and 31 P NMR and high‐resolution spectrometry and the functionalized nucleotides were characterized by LC/MS. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of phosphines Basic Protocol 2 : Synthesis of dinucleotides 4 and 5 Basic Protocol 3 : Synthesis of modified RNA 6 Basic Protocol 4 : Traceless Staudinger reactions on a dinucleotide Basic Protocol 5 : Traceless Staudinger reaction on RNA